Analisis Variabel Finansial dan Makroekonomi yang Berpengaruh terhadap Harga Saham (Studi di Bursa Efek Indonesia) - Atim Djazuli; Bambang Subroto; Made Sudarma; Arifin Sabeni (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research aimed to test and analyze the influence of financial variables (Return on Investment, Profit Margin, Current Ratio and Debt Ratio, Dividend, and Dividend Yield) and macroeconomic variables (Gross Domestic Product, Money Supply, Inflation, Currency, and Interest Rate) stock price altogether. This research used quantitative approach by implementing path analysis method. The research population is all companies listed in Indonesian Stock Exchange in the period of 2001–2007 out of which 52 companies were selected as samples to be observed within 7 (seven) years term resulting in as many as 364 observations. The results of this research indicate that the variables having an effect on dividend were Return on Investment and Net Profit Margin as well as interest rate. The variable having an effect on Dividend Yield were Current Ratio and Debt Equity Ratio and Gross Domestic Product. Furthermore, the variables affecting the interest rate were the Amount of Money Supply, Inflation, and American Dollar Rate to Rupiah. Next, the variables which influenced the stock price were Return on Investment, Current Ratio, Dividend, and Dividend Yield. Finally the variables which had insignificant influence were the variable of Gross Domestic Product to interest rate; the variable of Debt Equity Ratio to dividend; the variable of interest rate to stock price, and; the variable of Gross Domestic Product to stock price.Keywords: financial variables, macroeconomic variable, stock price.